FEA Based on 3D Micro-CT Images of Mesoporous Engineered Hydrogels - Siad, L.; Jing, J.; Braux, J.; Dubus, M.; Velard, F.; Laurent-Maquin, D.; Gangloff, S. C.; Kerdjoudj, H.; Rahouadj, R.; Schmidt, J. -F.; Ganghoffer, J. -F. (Engineering, Technology & Applied Science Research, 2015)
The objective of this computational study was to propose a rapid procedure in obtaining an estimation of elastic moduli of solid phases of porous natural-polymeric biomaterials used for bone tissue engineering. This procedure was based on the comparison of experimental results to finite element (FE) responses of parallelepiped so-called representative volume elements (rev) of the material at hand. To address this issue a series of quasi-static unconfined compression tests were designed and performed on three prepared cylindrical biopolymer samples. Subsequently, a computed tomography scan was performed on fabricated specimens and two 3D images were reconstructed. Various parallelepiped revs of different sizes and located at distinct places within both constructs were isolated and then analyzed under unconfined compressive loads using FE modelling. In this preliminary study, for the sake of simplicity, the dried biopolymer solid is assumed to be linear elastic.